2023
DOI: 10.3390/math11163612
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Sentiment and Luxury Behavior in the United States before and after COVID-19: Time Trends and Persistence Analysis

Berta Marcos Ceron,
Manuel Monge

Abstract: This paper analyzes the stochastic properties of consumer sentiment to understand how they affected the luxury sector in the United States before and after COVID-19. The results were derived using fractional integration methodologies and suggest that, before the pandemic episode, both variables were expected to be mean reverting and the shocks were transitory, having similar behavior. However, after the appearance of COVID-19, results suggest that consumer sentiment recovered before the luxury sector. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Studies have indicated that economic and financial crises such as COVID-19 have a negative impact on consumer sentiment, which translates into a decrease in consumption and greater sensitivity to prices. Crisis not only influences the economy, but also the behaviour, feelings, attitudes, motivations, emotions, and expectations of people (Marcos Ceron and Monge, 2023). Studies have also highlighted the permanent and irrevocable changes in consumers' tastes and preferences due to the pandemic and the resultant impact on the businesses such as a marked shift towards digital touchpoints and increased online interaction between firms and consumers (Kannan and Kulkarni, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that economic and financial crises such as COVID-19 have a negative impact on consumer sentiment, which translates into a decrease in consumption and greater sensitivity to prices. Crisis not only influences the economy, but also the behaviour, feelings, attitudes, motivations, emotions, and expectations of people (Marcos Ceron and Monge, 2023). Studies have also highlighted the permanent and irrevocable changes in consumers' tastes and preferences due to the pandemic and the resultant impact on the businesses such as a marked shift towards digital touchpoints and increased online interaction between firms and consumers (Kannan and Kulkarni, 2022).…”
Section: Introductionmentioning
confidence: 99%